Effect of home visit training program on growth and development of preterm infants a double blind randomized controlled trial - Edraki, Mitra (International journal of community based nursing and midwifery, 2015)
BACKGROUND: Home visit program can be effective in infants' growth and development. The present study aimed to investigate the effect of home visit program on preterm infants' growth and development within 6 months